Front Cover. Issue 12 (11th November 2020) - Bailey, Sarah A.; Brown, Lyndsay; Campbell, Marnie L.; Canning‐Clode, João; Carlton, James T.; Castro, Nuno; Chainho, Paula; Chan, Farrah T.; Creed, Joel C.; Curd, Amelia; Darling, John; Fofonoff, Paul; et al.
Abstract : The cover image relates to the Research Article https://doi.org/10.1111/ddi.13167 "Invasive coral Tubastraea tagusensis on the Ilha de Âncora, Armação dos Búzios, southeastern Brazil." Photography credit: Larissa Pires‐Teixeira.